The Longing of Women in The Girl on the Train by Paula Hawkins - Monika John Sujatha (ILN Journal: Indian Literary Narratives, 2025)
Abstract This research article attempts to read Paula Hawkins novel The Girl on the Train through the lens of Psycho – Feminism. By analyzing this text, the researcher argues that Hawkins not only captures the attributes of the thrillers but also secretly reveals the harsh treatment of society towards women in general, which make this novel fall under the category of Psycho -feminism. This field combines Psychological principles with Feminist Theory exploring how gender affects mental processes and social behavior. The study utilizes a multidisciplinary approach drawing on theories from Psychology and feminism to discuss how the mistreatment of society affects the mental stability of women. The paper reveals how Hawkins work serves as a powerful commentary on women oppression in the society.